Structural metamorphosis of graphitic derivatives produced from fractionated bamboo lignin - Ahmad Farid, Mohammed Abdillah; Lease, Jacqueline; Zheng, Alvin Lim Teik; Tsubota, Toshiki; Andou, Yoshito (American Chemical Society, 2023)
The demand for sustainable and renewable materials has prompted extensive research on lignocellulosic biomass as a potential feedstock for advanced nanomaterials. This article describes the sequential processes of iron-catalyzed graphitization, improved Hummer’s method, and low-temperature thermal annealing designed to transform ethanosolv lignin into bio-based graphene products. The lignin undergoes a metamorphosis during graphitization, transforming into turbostratic crystallite with a unique flake-like configuration at high temperatures in a tightly sealed muffle furnace. Following oxidation, the structure of the resultant graphite undergoes dynamic changes, leading to exfoliation-induced distancing of the sheets of graphene layers. Notwithstanding the reduction process, the geometrical morphology of its oxidized state remains unaltered, preserving the lamellar configuration. Notably, the resulting graphitized lignin showcases a substantial carbon content exceeding 75 wt and a relatively low oxygen content below 16 wt . In contrast, graphene oxides (GOs) exhibit elevated oxygen levels resulting from the introduction of oxygen moieties during the oxidation step, which subsequently diminishes following thermal annealing. Diffraction patterns confirm the presence of (001), (002), and (100) planes in all graphene-based materials, indicating an aromatic ring orientation. Oxidation affects interlayer spacing with GOs exhibiting larger distances than graphitized lignin and reduced graphene oxides (rGOs). Graphitization increases the sp2 carbon composition by removing volatiles and mineral matter. Oxidation increases the sp3 carbon composition, but it decreases after thermal annealing due to the partial removal of oxygen species, leading to a reorientation of the sp2 carbon configuration.